Design and experimental setup of a new concept of an aerosol-on-demand print head. Issue 4 (2nd March 2022) - Sieber, Ingo; Zeltner, David; Ungerer, Martin; Wenka, Achim; Walter, Tim; Gengenbach, Ulrich
Abstract: Aerosol jet printing is an alternative to inkjet printing, the currently most established fabrication technique for printed electronics, with the benefits of small feature sizes, more homogeneous thickness of the printed layers, and the possibility to print on 3D structures. Printers are available on the market, in which the aerosol is generated outside of the print heads, with the disadvantage that only continuous operation is possible due to the long distance between atomization unit and print head. We report on the development and validation of a new integrated principle, with the atomization of the ink directly inside the print head. This enables a compact design, printing in all spatial directions and jet-on-demand operation. Based on fluid dynamic simulations, an optimized integrated print head design was developed, and fabricated. First tests have been performed in a preliminary laboratory test setup. The successful focusing of the aerosol to approximately 1/7 of the spread of the non-focused aerosol spray was validated in experiments, thus confirming the operating principle of the new aerosol-on-demand print head.